The Response of Rhodotorula mucilaginosa to Patulin Based on Lysine Crotonylation - Yang, Qiya; Li, Yulin; Apaliya, Maurice T.; Zheng, Xiangfeng; Serwah, Boateng N. A.; Zhang, Xiaoyun; Zhang, Hongyin (Frontiers in Microbiology, 2018)
Patulin (PAT) is a mycotoxin produced by some Penicillium, Aspergillus, and Byssochlamys species. Rhodotorula mucilaginosa is able to degrade PAT in vivo as well as in vitro, up till date, the process and molecular mechanism(s) involved patulin degradation still remains unknown. Protein lysine crotonylation (Kcr) plays an important role in regulating chromatin dynamics, gene expression, and metabolic pathways in mammals and eukaryotes. Investigation of the Kcr changes accompanying degradation of patulin in R. mucilaginosa were observed to investigate the mechanisms of patulin inhibition. Tandem mass tag (TMT) labeling and Kcro affinity enrichment, followed by high-resolution LC-MS/MS analysis, were used to perform quantitative lysine crotonylome analysis on R. mucilaginosa. Consequently, 1691 lysine crotonylation sites in 629 protein groups were identified, among which we quantified 1457 sites in 562 proteins. Among the quantified proteins, 79 and 46 crotonylated proteins were up-regulated and down-regulated, respectively. The differentially up expressed modified proteins were mainly involved in tricarboxylic acid cycle and gluconeogenic pathway. The differentially down expressed Kcr proteins were mainly classified to ribosome and carbohydrate transport and metabolism. Bioinformatic analyses were performed to annotate the quantifiable lysine crotonylated targets. Moreover, interaction networks and high confidence domain architectures of crotonylated proteins were investigated with the aid of bioinformatic tools, and these results showed that there was an increase in the number of yeasts with crotonylated proteins. The results also provided information on the various roles of crotonylation, which are involved in PAT degradation.